If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6 = 6(x + 1) Reorder the terms: -6 + 6x = 6(x + 1) Reorder the terms: -6 + 6x = 6(1 + x) -6 + 6x = (1 * 6 + x * 6) -6 + 6x = (6 + 6x) Add '-6x' to each side of the equation. -6 + 6x + -6x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 0 = 6 + 6x + -6x -6 = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 = 6 + 0 -6 = 6 Solving -6 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| X^2+3y^2-12y+9=0 | | 14-7x=159-4x | | x/3-7=11 | | 58-x=(x+7) | | 2x+0=-5 | | 13.99(50-12)= | | -20x^5/10x^2 | | 1/4x-3=13 | | h=16t^2+320 | | -6x+4=-2x-12 | | 25x^4-20x^3/5x | | -8(x+2)-(9-6x)=-3 | | 7-3x/x+2+4x/x | | 8(y+3)+9(y+2)=y-3 | | 45/-5 | | 3x+7=059-8x | | a-2/6=5 | | 6/3-7=11 | | 2b^2*b^3= | | 3x+12=4x-4 | | 6x+3=4x-4 | | 2*0-y=-5 | | m+6= | | 10y+43+y^2/y+3 | | 5x-1=6x^2 | | 4n+19=43 | | c/6+2=-4 | | 4x^2-6x-3=21-6 | | 2x-3=4x+13 | | 2(7x-2)+9=14x+5 | | y^2+2y+8=5y+6 | | 4y-2=2y+28 |